The search for new diagnostic markers of metabolic response to aerobic exercise: analysis of creatinine, urea, and uric acid levels in football players - Nowak, Robert; Buryta, Rafał; Kostrzewa-Nowak, Dorota (Akademia Wychowania Fizycznego w Poznaniu)
Introduction. A football match as well as long-term football training are known to influence players’ cellular metabolism and can lead to muscle damage, oxidative stress as well as biochemical and hormonal changes. Aim of Study. Considering the importance of aerobic training for football players, the aim of this study was to evaluate changes in plasma creatinine, uric acid (UA), and urea levels in response to a semi-long distance outdoor run in aerobic conditions in both female and male football players. Material and Methods. 16 voluntarily recruited football players aged 22.50 (women) and 18.35 (men) years, took part in an outdoor run. The female players covered a distance of 7.4 ± 0.3 km, while the male players covered a distance of 10.7± 1.0 km. Plasma levels of the studied biochemical parameters were determined using an appropriate diagnostic assay kit. Results. Aerobic exercise did not influence the creatinine level of football players, whereas a significant decrease in median post-exercise UA level was found only in the group of female players. The outdoor run caused a systematic increase in urea plasma concentration during the experiment in both studied groups. Conclusions. The obtained results confirm that UA and urea blood plasma levels could be effective diagnostic markers for evaluation of metabolic response to aerobic exercise, at least among female athletes. The correlations found in this study point to urea as a potential marker of overtraining syndrome in athletes
Keywords: aerobic training; creatinine; outdoor run; urea; uric acid